2013
DOI: 10.1167/13.8.19
|View full text |Cite
|
Sign up to set email alerts
|

Two primes priming: Does feature integration occur before response activation?

Abstract: Responses to a target can be sped up or slowed down by a congruent or incongruent prime, respectively. Even though presentations are rapid, the prime and the target are thought to activate motor responses in strict sequence, with prime activation preceding target activation. In feature fusion, the opposite seems to be the case. For example, a vernier offset to the left is immediately followed by a vernier offset to the right at the same location. The two verniers are not perceived as two elements in sequence b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
(51 reference statements)
3
6
0
Order By: Relevance
“…It is important to point to the different insights that can be gained from an ANOVA on mean correct RT, versus an event history analysis. First, in accordance with the conclusions from previous findings (Breitmeyer & Hanif, 2008;Grainger et al, 2013), a second prime dominates the priming effect in mean correct RTs and ER, at least for short interprime intervals. However, the event history analysis showed that the first prime dominated the motor response in the earliest bins (Experiment 1).…”
supporting
confidence: 91%
See 3 more Smart Citations
“…It is important to point to the different insights that can be gained from an ANOVA on mean correct RT, versus an event history analysis. First, in accordance with the conclusions from previous findings (Breitmeyer & Hanif, 2008;Grainger et al, 2013), a second prime dominates the priming effect in mean correct RTs and ER, at least for short interprime intervals. However, the event history analysis showed that the first prime dominated the motor response in the earliest bins (Experiment 1).…”
supporting
confidence: 91%
“…Intermediate responses should be influenced by the second prime. From previous data, we expected that the second prime would dominate the response at the shortest P1-P2 SOA (i.e., the longest P2-T SOA), and this dominance of the second prime should decrease with increasing P1-P2 SOA because the first prime has progressively more time to activate a response before the second prime occurs, while the second prime has progressively less time before the target occurs (Grainger et al, 2013).…”
Section: Predictionsmentioning
confidence: 98%
See 2 more Smart Citations
“…The invisible vernier target offset is even integrated with offsets of flanking elements, which can be presented more than 400 ms after target onset, which is much longer than the reaction times in mask priming experiments. We have recently shown that feature fusion even precedes motor-priming (Grainger et al, 2013). As in the TMS experiment above, the sequential metacontrast paradigm shows that features of invisible elements can persist in the human brain for substantially long times.…”
Section: Review Of Evidencementioning
confidence: 98%